Corporate social responsibility and corporate financial performance: An empirical analysis of Chinese banks - Yang, Yuchen (2022)
Abstract Corporate social responsibility is defined as actions in which firms undertake social-good activities beyond the firm's interests to the extent permitted by law. This study analyses the relationship between Chinese banks' corporate social responsibility (CSR) and corporate financial performance (CFP). Secondary data has been collected from 44 Chinese banks listed in Shanghai and Shenzhen stock exchange for five years (2015-2019). The results indicate that social responsibility and its six dimensions positively impact Chinese banks financial performance. Moreover, in the context of Chinese special national conditions, the findings provide insight for managements to treat CSR as one of their core functions for improving financial performance, which helps them keep a strategic position in the business world.